The Influence of Parenting Patterns on the Character of Pre-School Children - Fatma Nadia; Komaria Susanti; Indah Lestari (Institute of Computer Science (IOCS), 2022)
One primary factor efficacy of education is the pattern of taking care of old fellows. Patterns take care of old fellows very having an effect on the growth of children. Each pattern takes care of existing old fellows, which will give different influences on child characteristics. Old fellows represent the environment closest which always circuit child at the same time become their idol and figure. The target of the research is to know the influence of the pattern take care of old fellows to pre-child characters going to school in Mardisiwi Kindergarten, Tapung Makmur Village, Kampar Regency Year 2020. Research type that is quantitative with method approach of cross-sectional. Research conducted in Mardisiwi Kindergarten, Tapung Makmur Village, Kampar Regency. The population in this research that is amounting to 41 by using totalizing sampling. Research instrument use questionnaire. Data analysis uses analysis of univariate bivariate and. From the result of the research influence of pattern take care of old fellow to pre-child character go to school in Mardisiwi Kindergarten, Tapung Makmur Village, Kampar Regency Year 2020 P-value 0.011. With the existence of this research is expected can add knowledge to parents about the influence of patterns take care of old fellows on school pre-child character.